The Impact of Extended Work Availability on Turnover Intention Among Generation Z in Indonesia - Mantana, Immanuel; Kurniadi, Nicholas; Astuti, Niken Dwi; Suryaatmaja, Kevin (Syntax Literate, 2025)
This research aims to examine the relationship between Work-Related Extended Availability (WREA) and Perceived Organizational Support (POS) on Turnover Intention (TI) among Generation Z employees in Indonesia. The study also analyzes the mediating roles of Emotional Exhaustion (EMO) and Work Engagement (WE), as well as the moderating roles of POS and WREA in these relationships. A quantitative approach was employed through an online survey distributed via Google Forms. Data were collected using purposive sampling from 310 Generation Z employees working across various industrial sectors in Indonesia. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS version 4 software. The findings indicate that WREA significantly increases EMO, which subsequently raises TI among Generation Z employees in Indonesia. Conversely, POS enhances WE and indirectly reduces TI. The moderating effect of WREA on the POS–WE relationship was significant, whereas the moderating effect of POS on the WREA–EMO relationship was not supported. This study extends the application of the Job Demands-Resources (JD-R) model within the context of Generation Z employees in Indonesia by simultaneously integrating mediation and moderation effects. Practically, organizations should limit WREA and strengthen support tailored to the digital needs of Gen Z employees to prevent emotional exhaustion and reduce turnover intention.